2009
DOI: 10.1117/12.815900
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear piezoelectric impedance modulation and its application to crack detection

Abstract: In this paper, a structural health monitoring (SHM) methodology that can detect and characterize local structural damages in early stage is developed, by merging the concepts of two existing SHM principles, a piezoelectric impedance-based methodology and a nonlinear wave modulation spectroscopy. The presented SHM system mainly consists of a piezoelectric element bonded on the structural surface, a high-frequency harmonic voltage source, and a current detector. When the structure is subjected to a dynamic load … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…(46), the damage evaluation index is defined as follows. Note that the damage index derived in this section is fundamentally the same as that described in the previous paper, 12 but the mathematical formulation is slightly modified.…”
Section: Damage Evaluation Indexmentioning
confidence: 97%
See 1 more Smart Citation
“…(46), the damage evaluation index is defined as follows. Note that the damage index derived in this section is fundamentally the same as that described in the previous paper, 12 but the mathematical formulation is slightly modified.…”
Section: Damage Evaluation Indexmentioning
confidence: 97%
“…Masuda et al 12 have proposed a self-sensing, novel integrity monitoring methodology, which can be sensitive to the incipient contact-type defects by combining the concepts of the NWM-based methodologies with the piezoelectric impedance-based methodologies. 13 It has been shown that, when the structure involving defects is subjected to a low-frequency vibrational load (pump), the coupled electro-mechanical admittance of the PE in high-frequency range is perturbed in synchronization with the low-frequency pump load, so that the current response flowing through the PE induced by the high-frequency harmonic probe voltage source is modulated both in amplitude and phase.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary tests (for detail see [45]) showed that, for a steel beam specimen with a fatal transverse crack initiated from a pre-produced notch made by electrical discharge machining (EDM), modulation was observed in the current response to the probe voltage of approximately 60 kHz, under a cyclic transversal pumping load of approximately 1 Hz applied by hand. In contrast, no visible modulation was found for intact specimens with or without the EDM notch.…”
Section: Overviewmentioning
confidence: 99%
“…For this reason, a simpler self-sensing technique, which requires merely a single piezoelectric active sensor, is desired. Masuda et al [43] have proposed a self-sensing, baseline-free SHM methodology, which can be sensitive to the incipient contact-type failures even in the hidden form, by combining the concepts of the PI-based and NWM-based methodologies. In this approach, a single piezoelectric active sensor is utilized just as the PI-based SHM setup, and driven by a high-frequency harmonic probe voltage.…”
Section: Introductionmentioning
confidence: 99%